Development of Discovery Learning Based Animation Video Media Assisted by the Doratoon Application on Theme 8 Sub-theme 1 Class V to Q.A 2022/2023 - Yesika Simanullang; Ananda, Lala Jelita; Gultom, Ibrahim; Tamba, Robenhart; Gandamana, Apiek (Indonesian Journal of Advanced Research, 2023)
The aim of this research is to produce Doratoon learning media products that are valid, practical and effective for class V students at SDN 101765 Bandar Setia. This type of research is Research and Development (R&D) research which uses the ADDIE development model. The steps in this research and development are Analyze, Design, Development, Implementation and Evaluation. The trial subjects consisted of material experts, media experts, class V teachers and 25 students for field trials. Data collection techniques in this research are observation, interviews, questionnaires and tests. The data analysis techniques in this research are qualitative descriptive analysis techniques and quantitative descriptive analysis techniques. The results of media development assisted by the Doratoon application show: (1) The overall validation results of material experts show that the learning media is declared very valid (85%) and the overall media validation results for qualifications are very valid (90%); (2) The results of the teacher's practicality as a whole show that the learning media is stated to be very practical (90%); (3) The results of the effectiveness test have an average value of 87.8 with the completeness criterion "Complete". It can be concluded that the learning media assisted by the Doratoon application developed by researchers is very feasible, very practical, and very effective for use with class V students at SD Negeri 101765 Bandar Setia.